“To Permit or Not to Permit” — Tools for Reforming Permits and Licensing Systems - Ibragimov, Sanjar; Taymetov, Bobir (World Bank, Washington, DC, 2012)
This SmartLesson discusses the experience in permits and licensing reforms undertaken in a number of countries of Eastern Europe and Central Asia. It seeks to contribute to International financial corporation's (IFC's) knowledge bank of business enabling environment reforms, within the context of developing the global product on licensing. The distinctions between licenses and permits are blurred, and the terms are often used interchangeably.